A comparison of postoperative pain between transumbilical and suprapubic incision in laparoscopic liver resection. Issue 3 (15th April 2022) - Soyama, Akihiko; Murakami, Shunsuke; Natsuda, Koji; Hara, Takanobu; Matsuguma, Kunihito; Matsushima, Hajime; Imamura, Hajime; Tanaka, Takayuki; Adachi, Tomohiko; Hidaka, Masakaki; Eguchi, Susumu
Abstract: Background: In laparoscopic liver resection, few reports have investigated the influence of type of incision on postoperative pain in laparoscopic liver resection. We therefore conducted the present study to clarify the difference in postoperative pain between two types of incision. Methods: Nineteen patients who underwent laparoscopic lateral sectionectomy were enrolled. In 11 patients with a transumbilical incision and eight with a suprapubic incision, the operation duration, blood loss, length of incision, duration of intravenous fentanyl infusion immediately after surgery and rescue dosage, and period of regular oral nonsteroidal anti‐inflammatory drugs were evaluated. Results: There was no significant difference between the two groups in patients' background characteristics, operation time, or amount of blood loss. The length of suprapubic incision was significantly longer than the umbilical incision. Concerning the postoperative pain management, the duration of intravenous fentanyl administration was 1 day (1–2 days) for umbilical incisions and 1.5 days (1–2 days) for suprapubic incisions, showing no significant difference. Regarding the rescue dosage of fentanyl, the results were comparable between the groups. Regarding the postoperative duration of regular nonsteroidal anti‐inflammatory drug administration, there was also no significant difference between the groups (transumbilical: 14 [5–35] days vs suprapubic: 8 [7–32]). Conclusions: Postoperative pain is comparable between umbilical and suprapubic incision in patients who underwent laparoscopic left lateral segmentectomy. In terms of postoperative pain, either a transumbilical incision or a suprapubic incision can be selected for specimen extraction.